2021
DOI: 10.1200/jco.2021.39.15_suppl.e16239
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of LDE225 in combination with gemcitabine and nab-paclitaxel in patients with metastatic pancreatic cancer.

Abstract: e16239 Background: In pancreatic ductal adenocarcinoma (PDAC) desmoplasia is a central feature of the tumor microenvironment. By targeting both tumor cells and tumor stoma, treatment efficacy can be increased. LDE225 is a pharmacological Hedgehog signaling pathway inhibitor and is thought to specifically target tumor stroma. We investigated the combined use of LDE225 and chemotherapy in PDAC patients. Methods: The objective of phase I of the study was to established the maximum tolerated dose (MTD) of LDE225 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A phase II study concluded that the combination of Vismodegib did not work well chemotherapy agents such as gemcitabine and nab-paclitaxel [ 111 ]. Another SMO inhibitor Sonidegib was utilized in combination with gemcitabine and nab-paclitaxel and showed tolerance in PDAC patients in a phase II study [ 112 ]. Saridegib targeting Hh pathway via SMO revealed mixed outcomes in two studies for PDAC patients with one showing poor effect on survival [ 113 ] and the other showed good tolerance in combination with gemcitabine [ 114 ].…”
Section: Targeted Therapeutic Approachesmentioning
confidence: 99%
“…A phase II study concluded that the combination of Vismodegib did not work well chemotherapy agents such as gemcitabine and nab-paclitaxel [ 111 ]. Another SMO inhibitor Sonidegib was utilized in combination with gemcitabine and nab-paclitaxel and showed tolerance in PDAC patients in a phase II study [ 112 ]. Saridegib targeting Hh pathway via SMO revealed mixed outcomes in two studies for PDAC patients with one showing poor effect on survival [ 113 ] and the other showed good tolerance in combination with gemcitabine [ 114 ].…”
Section: Targeted Therapeutic Approachesmentioning
confidence: 99%